Impact of Stokes Shift on the Performance of Near-Infrared Harvesting Transparent Luminescent Solar Concentrators. Issue 1 (December 2018) - Yang, Chenchen; Zhang, Jun; Peng, Wei-Tao; Sheng, Wei; Liu, Dianyi; Kuttipillai, Padmanaban; Young, Margaret; Donahue, Matthew; Levine, Benjamin; Borhan, Babak; Lunt, Richard
Abstract Visibly transparent luminescent solar concentrators (TLSC) have the potential to turn existing infrastructures into net-zero-energy buildings. However, the reabsorption loss currently limits the device performance and scalability. This loss is typically defined by the Stokes shift between the absorption and emission spectra of luminophores. In this work, the Stokes shifts (SS ) of near-infrared selective-harvesting cyanines are altered by substitution of the central methine carbon with dialkylamines. We demonstrate varyingSS with values over 80 nm and ideal infrared-visible absorption cutoffs. The corresponding TLSC with such modification shows a power conversion efficiency (PCE ) of 0.4% for a >25 cm2 device area with excellent visible transparency >80% and up to 0.6% PCE over smaller areas. However, experiments and simulations show that it is not the Stokes shift that is critical, but the total degree of overlap that depends on the shape of the absorption tails. We show with a series ofSS -modulated cyanine dyes that theSS is not necessarily correlated to improvements in performance or scalability. Accordingly, we define a new parameter, the overlap integral, to sensitively correlate reabsorption losses in any LSC. In deriving this parameter, new approaches to improve the scalability and performance are discussed to fully optimize TLSC designs to enhance commercialization efforts.